2017
DOI: 10.1080/13546783.2017.1384760
|View full text |Cite
|
Sign up to set email alerts
|

The link between deductive reasoning and mathematics

Abstract: Recent studies have shown that deductive reasoning (including transitive and conditional inferences) are related to mathematical abilities. Nevertheless, so far the links between mathematical abilities and these two forms of deductive inference have not been investigated in a single study. It is also unclear whether these inference forms are related to both basic maths skills and mathematical reasoning, and whether these relationships still hold if the effects of fluid intelligence are controlled. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 60 publications
4
34
1
1
Order By: Relevance
“…In the field of mathematics education, the study of deductive reasoning has been mainly associated with mathematical proof, leaving the understanding of deductive reasoning, per se, in the background [20,21]. This may have to do with the diverse ways of conceiving deductive thinking by the protagonists involved in mathematics education.…”
Section: Logical Reasoning and Mathematics Learningmentioning
confidence: 99%
“…In the field of mathematics education, the study of deductive reasoning has been mainly associated with mathematical proof, leaving the understanding of deductive reasoning, per se, in the background [20,21]. This may have to do with the diverse ways of conceiving deductive thinking by the protagonists involved in mathematics education.…”
Section: Logical Reasoning and Mathematics Learningmentioning
confidence: 99%
“…Yet, acquiring math skills also involves understanding relations between quantities and drawing inferences based on these relations (Singley and Bunge 2014). In keeping with this idea, recent behavioral studies suggest that understanding relations of transitivity may significantly contribute to math learning in children (Handley, Capon et al 2004, Morsanyi, Devine et al 2013, Morsanyi, Kahl et al 2017, Morsanyi, McCormack et al 2017). Here we tested whether the brain representations of transitive relations may predict current and future math skills in children.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Handley et al (2004) showed that numeracy and arithmetic skills are positively correlated with logical (including transitive) reasoning performance in 10-year-olds. Morsanyi and colleagues further found a specific relationship between transitive reasoning performance and mathematical abilities in adolescents and adults (Morsanyi et al, 2017; Morsanyi et al, 2018). Therefore, the literature suggests that inter-individual differences in math skills may relate to inter-individual differences in transitive reasoning skills.…”
Section: Discussionmentioning
confidence: 99%